2016
DOI: 10.1016/j.psym.2016.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Capacity Evaluations of Psychiatric Patients Requesting Assisted Death in the Netherlands

Abstract: Objective Euthanasia or physician-assisted suicide (EAS) of psychiatric patients is legal in some countries but remains controversial. This study examined a frequently raised concern about the practice: how physicians address the issue of decision-making capacity of persons requesting psychiatric EAS. Methods A review of psychiatric EAS case summaries published by the Dutch Regional Euthanasia Review Committees. Directed content analysis using a capacity-specific 4 abilities model (understanding of facts, ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(53 citation statements)
references
References 25 publications
2
50
0
1
Order By: Relevance
“…Such a conflict or dynamic between alleviating suffering and preventing harm by suicide is also visible in the Dutch policy and mental health context, where, on the one hand, suicide is high on the political agenda but, on the other hand, in cases of unbearable suffering that cannot be treated anymore in the opinion of psychiatrists physician-assisted suicide is allowed also for people with mental illnesses [39][40][41]. A recent newspaper article has suggested that psychiatrists in particular, compared to other physicians, are very reluctant to participate in euthanasia, even when they acknowledge unbearable suffering, with people with psychiatric illnesses who have a death wish more likely to seek help with the Dutch End of Life Clinic ('Levenseindekliniek'), compared to people with for instance terminal cancer or dementia who are more likely to be helped through routes other than this 'last resort' [42].…”
Section: The Duty Of Care and The Duty To Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a conflict or dynamic between alleviating suffering and preventing harm by suicide is also visible in the Dutch policy and mental health context, where, on the one hand, suicide is high on the political agenda but, on the other hand, in cases of unbearable suffering that cannot be treated anymore in the opinion of psychiatrists physician-assisted suicide is allowed also for people with mental illnesses [39][40][41]. A recent newspaper article has suggested that psychiatrists in particular, compared to other physicians, are very reluctant to participate in euthanasia, even when they acknowledge unbearable suffering, with people with psychiatric illnesses who have a death wish more likely to seek help with the Dutch End of Life Clinic ('Levenseindekliniek'), compared to people with for instance terminal cancer or dementia who are more likely to be helped through routes other than this 'last resort' [42].…”
Section: The Duty Of Care and The Duty To Reportmentioning
confidence: 99%
“…Leeman argues that psychiatrists owe it to their patients to treat each of their situations as unique, thus not immediately dismissing every case of suicidal ideation as irrational (see also Hewitt 2010). Interestingly however, recent evidence on capacity evaluations of psychiatric patients in the Netherlands who request euthanasia points to an opposite trend, where psychiatrists presume capacity (and thus rationality) despite evidence of a mental illness present that could cloud a patient's judgment [39].…”
Section: Subjectivitymentioning
confidence: 99%
“…These statistics raise questions regarding the role of psychiatrists in administering voluntary active euthanasia or physician aidin-dying and the evaluation of capacity, because a large number of the physicians who administered voluntary active euthanasia were psychiatrists and less than half of the case subjects with a psychiatric diagnosis had a second opinion from a psychiatrist. Another review of these same 66 case subjects concluded that there was no evidence of a mandatory high threshold of patient capacity before administration of euthanasia (14). Documentation of capacity-specific criteria among these case subjects has shown that 55% demonstrated global assertion of capacity and 46% had at least one capacity-specific ability (e.g., understanding information, ability to reason, or appreciation of the consequences to self ), but there is no evidence that all four Appelbaum capacity criteria were met (14, 15) (see box).…”
Section: Assessment Of Capacity and Evaluation For Psychiatric Disordersmentioning
confidence: 99%
“…In the United States, because physician aid-in-dying is approved on a state level, there is variability in the regulatory agencies overseeing the practice. Lack of strict regulations in the Netherlands has led to cases in which medically assisted suicide was done for patients with impaired cognition or psychiatric disorders (14) and to extension of the practice among vulnerable populations (9). Thus, what should the role of psychiatrists be in ensuring that depression is adequately screened among individuals requesting physician aid-in-dying?…”
Section: Further Considerationsmentioning
confidence: 99%
“…EAS for mental suffering has been fiercely debated. Arguments have focused on the difficulty of assessing the patient’s subjective perception and complaints and on the challenges in assessing the patient’s capacity of judgement, which may be impaired by psychiatric conditions such as severe depression [ 10 12 ]. Arguments in favour of including both mental and physical suffering as legally acceptable grounds for EAS focus on the fact that a key objective of such legislation is to relieve suffering.…”
Section: Introductionmentioning
confidence: 99%